Enhancing the removal of pollutants from coke wastewater by bioaugmentation: a scoping study - Raper, Eleanor; Stephenson, Tom; Simões, Francisco; Fisher, Raymond; Anderson, David R.; Soares, Ana (Cranfield University, 2018)
BACKGROUND Bioaugmentation and biostimulation were investigated for their ability to improve the removal of thiocyanate (SCN-), polycyclic aromatic hydrocarbons (PAHs), phenol and trace metals in coke wastewater. Additionally, the ability of the microorganisms supplemented with the bioaugmentation product to survive in a simulated river water discharge was evaluated. RESULTS A commercially available bioaugmentation product composed mainly of Bacillus sp. was mixed with activated sludge biomass. A dose of 0.5 g/L increased the removal of Ʃ6PAHs (sum of fluoranthene, benzo[b]fluoranthene, benzo[k]fluoranthene, benzo[a]pyrene, indeno[1,2,3-cd]pyrene and benzo[g,h,i]perylene) by 51% and reduced SCN- below 4 mg/L enabling compliance with the EU Industrial Emissions Directive (IED). Biostimulation (supplementing micronutrients and alkalinity) allowed compliance for both SCN- and phenol (<0.5 mg/L). Bacillus sp. accounted for 4.4% of the microbial population after 25 hours (1.5 g/L dose) which declined to 0.06% after exposure to river water (24 hours). Exposure of the activated sludge biomass to river water resulted in a 98.6% decline in viable cell counts. CONCLUSION To comply with the IED, bioaugmentation and biostimulation are recommended for the treatment of coke wastewater to enable an effluent Ʃ6PAHs of 6.6 μg/L, 0.3 mg/L phenol and 1.2 mg/L SCN-. Such techniques are not anticipated to impact on downstream river water quality.
Keywords: Bioaugmentation; Biostimulation; Thiocyanate; Phenol; Trace metals; Polycyclic aromatic hydrocarbons